(untitled) (Medical Forum Monthly, 2020)
Objective: To study the A mutual relationship Ultrasonic value fetal weight and acute birth weight of neonate in Pakistan. Study Design: Observational study Place and Duration of Study: This study was conducted at the Radiology Department of Lahore General Hospital, Lahore and Idris Teaching Hospital Sialkot from Jan 2019 to July 2019. Materials and Methods: The patients of 37th week of gestation and over were added in the study to compare the acute the weight of a baby and Ultrasonography estimated weight of the fetus. Total 282 pregnant ladies with no complication history were sorted for the study as a sample. The history medical examination and ultrasonic examination were considered in every patient. The informed consent was also taken from every pregnant woman. The permission of the ethical committee was also considered. Results: The advancement in technology has helped to improve public health in reducing the risk of mortality in women and in neonates. The study reveals that there is no significant difference between the value of the weight of a baby calculated in Ultrasonography and the real weight delivered at birth time. Conclusion: It can be concluded from the results that the ultrasound is a safe and good predictor of birth weight and its readings and results can help in important decision by the gynecologist for safer delivery.